Peran Pustakawan Bagi Siswa Tunarungu dalam Pemanfaatan Perpustakaan di Sekolah Dasar Luar Biasa Painan Provinsi Sumatera Barat - Senova Haripal; Desriyeni Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
This paper discussed on the Role of Librarians for the Deaf students in the use of the Library in Primary Schools Exceptional West Sumatra province. This paper aims to describe (1) the role of librarians for deaf students in the use of libraries in elementary schools Extraordinary West Sumatra province, (2) what barriers faced by librarians for deaf students in the use of libraries in elementary schools Extraordinary West Sumatra province, and (3) the efforts of librarians for deaf students in the use of libraries in elementary schools Extraordinary West Sumatra Province. Based on the results of this study concluded that (1) the role of Librarians for the Students Deaf in Utilization of Libraries in Primary Schools Extraordinary Painan West Sumatra province is helping to enrich the learning experience, inculcate the habit of independent learning, helping to accelerate the process of mastering reading techniques, helping the development of language skills, (2) what obstacles are faced by librarians for deaf students in the use of libraries in elementary schools Extraordinary Painan West Sumatra province is interest in reading is still lacking, collection is not adequate, the lack of facilities and infrastructure, (3) what efforts do librarians to overcome obstacles for deaf students in the use of libraries in elementary schools Extraordinary Painan West Sumatra province is inviting students to come to the library to read, the addition of the collection, adding facilities and infrastructure.Keyword: librarians, deaf students, library